MEMINIMUMKAN AGENCY PROBLEM DAN AGENCY COST DENGAN MENGGUNAKAN KONSEP ISLAM TENTANG PERUSAHAAN: ANTARA TEORI DAN PRAKTIK - Moh Khoiruddin; Vitradesie Noekent (Jurnal Ekonomi & Keuangan Islam, 2011)
Theoritically, a company based on the principles of Islamic law (profit and loss sharing/PLS) is believed to be able to minimize agency problems and agency cost than the conventional companies,either in the aspect of the business philosophy, contract design, and control. However, the implementation of PLS is still facing a lot of obstacles, Hence, it is not surprising that models of PLS is not predominantly used by Islamic financial institutions, both in Indonesia and abroad. The cclassic argument on Â why the model is not dominant because it is considered more risky. In order to contribute to the agency problems in the Islamic perspective, this paper, firstly, will explain and explore the arguments which show advantages of Islamic concept on company in reducing agency problems and agency cost. Secondly, this paper will reveal the obstacles and problems faced in the implementation of such concept. Thirdly, this paper will offer an alternative solution framework to address various issues and constraints faced by them. Solutions offered here includes understanding aspects of the Islamic business draft, micro and macro benefits, human resources, regulatory and performance measurement indicators of Â Islamic financial institutions.